The effect of maximal strength and plyometric training on physical performance of young football players and game intensity - Asadi, Mostafa (2020)
Football is a sport that is played in every country and it is considered as an intermittent activity involving sudden actions such as tackling, jumping, kicking, change of direction, and short distance sprinting. Aerobic and anaerobic power are important for football players. Nevertheless, strength, power and speed are the most important qualities for athletic performance. Strength training (ST) and plyometric training (PT) are two frequently used methods for improving sport performances. The aim of this study was to examine the effect of maximal strength and plyometric training on physical performance of young football players and game intensity.